Individual and contextual determinants of resident-on-resident abuse in nursing homes: A random sample telephone survey of adults with an older family member in a nursing home. Issue 2 (September 2015) - Schiamberg, Lawrence B.; von Heydrich, Levente; Chee, Grace; Post, Lori A.
Highlights Study examined determinants of resident-on-resident abuse (RRA) in nursing homes. Age inversely related to RRA, with mobile younger residents more likely to experience it. Limitations in both ADLs and IADLs were related to the likelihood of RRA. Institutional violence, in the form of all types of staff abuse, increased likelihood of RRA. Resident emotional closeness to family had unintended consequence of increasing RRA.